Influência da temperatura na ocorrência de pólens não reduzidos em batata diplóide - Rosa, Sandra Salazar da (2007)
Unreduced (2n) pollen grains are important in potato breeding, making possible through sexual polyploidy, to introgress genes from different ploidy levels. The purpose of this work was investigate the effect of temperature on 2n pollen grains occurrence in the diploid clones DLB1-140 and DLB1-150 and pollen sterility in the tetraploid cultivar Atlantic. Tubers were planted in growth chamber at 25ºC ± 2ºC and 16h day. Just before the beginning of flowering the plants were transferred to another growth chamber and maintained at the temperatures of 10, 15, 20, 25, 30 and 35ºC ± 2ºC; 10 plants of each clone and treatment were cultivated and the frequency of pollen sterility (empty grains) was quantified with acetocarmin staining at 2%. Pollen grain diameter was also measured in diploid clones. Pollen samples were taken from one flower of one anther and 1000 pollen grains were analyzed and classified as viable and sterile (empty. Pollen diameter of diploid clones was measured: 20,0mm size was considered as normally reduced 22,5mm, as unreduced (2n); and, in lower frequencies, the sizes of 25,0mm, 27,5 and 30,0mm were found. Kruskal-Wallis test at 5% indicated higher frequency of 22,5mm size at 15ºC (mean 30,70%) in the DLB1-140 clone and (mean 7,65%) in the DLB1-150 clone. Wilcoxon test showed that DLB1-140 clone had higher frequency 22,5mm pollen grains than DLB1- 150 in all treatments. DLB1-150 clone and Atlantic had higher pollen stainability at 15ºC and the clone DLB1-140 at 20ºC. In all clones analyzed pollen stainability increased with temperature during microsporogenesis